Por uma teoria sistêmica da memória jurídico-política: desaparecimento forçado, comissão nacional da verdade e estado constitucional de direito no Brasil - Leite, Tiago Medeiros (2022)
Doctoral research gets to search to construct a systemic theory of memory concerning of Brazilian political, sociological and legal realities in contemporary modernity time, presents as the goal central by observation to analyze the function of the National Truth Commission for the construction of the Constitutional State of Laws and truth in contemporary Brazil. Approaches a complex political, sociological and legal phenomenon, especially from cases of forced disappearance and the looks for victims in Brazil. The research opts for the dialectical method, setting observations on official documents of a political and normative types, historical facts and productions of other researchers. The paper is divided about four sessions: the first one makes observations about the construction of truth for the scientific world, discussing over conceptual elements about the scientific observer and the operation of observing, on memory, truth and reality from the scientific perspective; the second session treats about the National Truth Commission, the historical degrees of authoritarianism in Brazil, remarking the construction of instruments at the period of reestablishment of democracy in the country until the presentation of the final results of the Commission; the third session demands on observations on the development and conceptualization of forced disappearance at the international level, observing the consolidation of the human being as a subject of rights and obligations in the international order, the research aims to understand the practice of this international crime, particularly the crimes of the Military Dictatorship in Brazil and the urgency of the International Convention for the Protection of whole people against forced disappearances, their political/legal records and the relationship of these treaties with the precedents of the Inter-American Court of Human Rights; the fourth session reports as an observation about the memory and the right to know the truth and its relations with the Constitutional Rules in Brazil, the persecution for truth as a mechanism for transitional justice to democracy and the actions of missing persons and their relatives in the search for explanations over on violations of rights. The observations try to construct an elucidation about the perspective of the Brazilian Truth Commission actions some role for law and its connection with politics and sociology concerned of contemporary national reality. The conclusion is in the sense of recognizing the contributory function that the National Truth Commission implements in the consolidation of the Constitutional State of Law in Brazil, from the exercise of the Right to the Truth of the victims of Brazilian authoritarianism, also as the reaction contrary to this consolidation of the Constitutional State of Law in Brazil, from the exercise of the Right to the Truth of the victims of Brazilian authoritarianism, as the reaction contrary to this consolidation and the difficulty of conceptualizing the nomenclatures used by the transition to democracy by the Brazilian legal system as well.